SIMULATOR KUBIKEL MINIMUM UNTUK INVESTIGASI GANGGUAN SCADA SISTEM DISTRIBUSI TENAGA LISTRIK 20 KV - Prasetiyo, Wahyu Adi; Winarno, Heru (Gema Teknologi, 2014)
Wahyu Adi Prasetiyo, Heru Winarno, in this paper explain that with the SCADA system delivery and processing of data from substation equipment consisting of equipment protection, control and measurement becomes faster known by the operator (dispatcher). Measurement and status information indicative of the electric power system are collected in RTU is placed in the substation (GI) which is then sent to the SCADA Master Station.Kinerjasistem dipengaruhiolehpopulasigangguan happened. The more the population of nuisance, then it will significantly reduce the level of reliability of the distribution network which is under the control of the SCADA system. SCADA interference in the distribution of electrical power distribution systems 20 kV affect the level of reliability of the distribution network. Especially if the disturbance of the telecontrol Circuit Breaker. To repair SCADA telecontrol especially the disruption of the necessary investigative trials open close CB, but in emergency situations CB load shedding can not be done with the many considerations. Simulator cubicles with Circuit Breaker Dummy serves to replace the function of the actual CB in order to do the test cubicles control of SCADA without load shedding. By removing the SCADA communication in cubicles and then move it to the CB Dummy testing/investigation disorder can be performed optimally. This tool is equipped with IED Digital Meter Relay Protection and SCADA based so that in addition to the investigation failed control can also be used for investigations and telesignal telemetering disorders. Keywords: scada, investigations, reliability.